2014
DOI: 10.5114/pg.2014.47895
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression, cognitive coping strategies, and health locus of control in patients with digestive system cancer

Abstract: IntroductionContemporary psycho-oncology focuses on the study of the psychological determinants of the functioning of cancer patients. Among the psychological factors that significantly affect the functioning of the patients are anxiety and depressive disorders.AimTo assess the psychological functioning of patients with digestive system cancer in the cancer-treating process and to develop guidelines for psychological care dedicated to this group of patients based on the results of the study.Material and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…35 Other studies examining the effect of helplessness on symptom severity and difficulty in persisting in the face of medical adversity (e.g., cancer, HIV/AIDS) have similarly found that the construct of helplessness may be a factor underlying poor adaptation to life's difficulties in general, and more likely to result in anxiety, depression, and a passive coping style. 36,37 Additionally, both helplessness and magnification were related to mental health QOL and depression, whereas only magnification was associated with physical health QOL. Quality of life measures assess perceptions of overall health and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…35 Other studies examining the effect of helplessness on symptom severity and difficulty in persisting in the face of medical adversity (e.g., cancer, HIV/AIDS) have similarly found that the construct of helplessness may be a factor underlying poor adaptation to life's difficulties in general, and more likely to result in anxiety, depression, and a passive coping style. 36,37 Additionally, both helplessness and magnification were related to mental health QOL and depression, whereas only magnification was associated with physical health QOL. Quality of life measures assess perceptions of overall health and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…However, many experience depression following the initial reactive responses of denial, anger, and bargaining. Helplessness and lack of control over cancer progression or treatment can increase the severity of depression (Kulpa, Kosowicz, Stypula-Ciuba, & Kazalska, 2014). Young mothers experience depression as they realize that they are losing the motherhood they had pictured for themselves, and in some cases, they prepare for the ultimate loss of motherhood through death.…”
Section: Depressionmentioning
confidence: 99%
“…29,30 Similar results were found with helplessness, probably subsequent to a repercussion of poor adaptation to life's difficulties in general and their consequences, such as anxiety, depression, and passive coping style. 31 Another finding of our study is that, when considering only the CP patients, those with CS had also higher scores than those without CS; the difference is greater for the magnification and helplessness sub-scales than for the rumination.…”
Section: Pain Catastrophising Scalementioning
confidence: 48%